Dreams of Gain Without Pain : The Affective Allure of Pinterest’s Studyinspo Phenomenon - Pitkänen, Ella (My University, 2023)
Studyinspo – a portmanteau of the words “studying” and “inspiration” – is a name for a loose online community wherein users on different social media platforms document and share their academic pursuits in photographic form and access the content created by others, all in order to inspire and draw inspiration from one another. One of the most peculiar characteristics of the phenomenon is the distinctive visual look of the content associated with it. Not only is Studyinspo imagery easily recognisable due to its focus on certain subject matters – most notably, study-related everyday items such as books, note pads, and writing utensils – but the feeling one is imparted with when encountering these images is that of an almost overwhelming pleasure. In these photographs, typically quite unremarkable objects are portrayed in a highly attractive manner, and the harmonised compositions they form evoke a deep sense of satisfaction within the viewer. Even when cluttered writing desks or pages after pages of hand-written notes are depicted, the content circulating within the community remains inexplicably pleasant to look at. Studyinspo imagery’s peculiar effect on us poses various questions to those interested in the relationships between people and digital media. Why do these images make us feel this way, and why has a community like this formed in the first place – especially around studying? In this master’s thesis, these questions will be answered through phenomenological media analysis, drawing dominantly from the insights of French philosopher Maurice Merleau-Ponty. By examining Studyinspo imagery as it exists on image-centric social media platform Pinterest, it will be demonstrated that the phenomenon’s appeal is based on the haptic dimensions of individual photographs – particularly their smoothness and orderliness – which the viewer experiences both as a visual fact and as a deeply pleasurable tactile affect. Furthermore, as an exploration of the neoliberal realities of contemporary education systems in the USA and Europe reveals, engaging with virtual content that depicts studying as a deeply pleasurable activity serves a clearly defined purpose. In a world where the mental wellbeing of students is at all-time low, the pleasure emanating from Studyinspo images relieves the community member’s mental anguish and encourages them to continue their pursuits in hopes of attaining the same sense of enjoyment in their personal lives. Ultimately, it will be argued that what Studyinspo content on Pinterest provides are dreams of gain without pain – attractive glimpses into a world which, for as long as the realities dictating the Studyinspo enthusiasts’ lives remain the same, will unfortunately remain out of reach.
Keywords: phenomenology, photography, Pinterest, social media, studying